Pond mud - the small-scale farmers' fertilizer bag - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Putting farm by-products through a fish pond is the most effective way to recycle farm wastes. The pond becomes the fertilizer factory and the pond mud the fertilizer. Crops fertilized with pond mud, rather than composted crop material, give better...